Wearing Off Effect of OnabotulinumtoxinA Near the End of Treatment Cycle for Chronic Migraine: A 4‐Year Clinical Experience. Issue 2 (22nd November 2019) - Khan, Fawad A.; Mohammed, Alaa E.; Poongkunran, Mugilan; Chimakurthy, Anilkumar; Pepper, Michael
Abstract : Introduction: The injection interval for onabotulinumtoxinA (BoNTA) in the management of chronic migraine (CM) is 12 weeks (78‐84 days). The aim of this study was to review patient‐reported wearing off effect (WOE) of the therapeutic benefit of BoNTA near the end of the treatment cycle. We intended to describe the demographics of patients at baseline and compare groups of patients with multiple episodes of WOE. Methods: We conducted a retrospective review of patients with CM who received uninterrupted BoNTA therapy from January 2014 to March 2018. The data from patient‐reported WOE (worsening headache variables and neck pain) that occurred during the 4 weeks (28 days) prior to the scheduled re‐injection of BoNTA for treatment cycles with injection interval ≤13 weeks and without obvious confounding factors were reviewed. Results: We identified 98 eligible patients and analyzed 471 treatment cycles. Forty‐three unique patients reported at least 1 occurrence of WOE. About 24/43 patients reported 1 WOE event and 19/43 patients reported ≥2 WOE events. Between the 2 groups, anxiety disorder and opioid use for headache were statistically significantly different. In the former group, the median interquartile range (IQR) dose of BoNTA was 165 (155, 175) units and the median IQR duration of the antinociceptive effect of BoNTA was 66.5 (63, 71.5) days. In the latter group, the median IQR dose of BoNTA was 167 (155, 173.3) units and the median IQR duration of the antinociceptive effect of BoNTA was 65.3 (62.5, 68.8) days. Up to 32% of these patients reported an increase in the use of abortive therapies to manage the symptoms of WOE. Discussion: The primary goal of BoNTA in the treatment of CM is to mitigate the development of central sensitization. Since the 12‐week injection paradigm may not provide sustained antinociceptive effect in all patients, it may account for the failure of response to BoNTA. Repeated occurrences of the WOE can potentially lead to medication overuse and impact quality of life.